Detection and Cloning of a Gene Involved in Zwitermicin A Synthesis from Plant Growth Promoting Rhizobacteria of Bacillus sp CR64 - Wahyudi, Aris Tri; Astuti, Rika Indri; Mubarik, Nisa Rachmania; Faulina, Sarah Asih (Indonesian Journal of Biotechnology, 2010)
Utilization of soil bacteria as biocontrol agent is becoming popular due to its valuable and effective mechanisms to suppress plant pathogenic microbes. We have previously isolated Bacillus sp, designated as Bacillus sp CR64, which exhibited effective plant growth promoting and antifungal activities. In this study, CR64 was examined in inhibiting the growth of Rhizoctonia solani, the causing agent of root rot disease. Partial sequence analysis of 16S rRNA gene revealed that this isolate similar with Bacillus cereus (94%). Furthermore, a gene designated zmaR was detected by means of specific amplification of DNA fragment approximately 950 bp. This fragment was then cloned onto pCRII-TOPO (3.9 kb) and sequenced using DNA sequencer ABI PRISM 310. Sequence analysis revealed that it had highest homology with the ZmaR protein (89% identity; 90% similarity) of B. thuringiensis serovar kurstaki (AAF82729.2). Alignment analysis with other ZmaR sequences from other antibiotic-producing Bacilli exhibited an almost fully conserved region within ZmaR sequences.Key words : PGPR, Bacillus sp CR64, Zwitermicin A, Cloning, Antifungal.